2007
DOI: 10.1186/1471-2407-7-153
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant trastuzumab in the treatment of her-2-positive early breast cancer: a meta-analysis of published randomized trials

Abstract: Background: Breast cancer is the most common cancer in women in the U.S. and Western Europe. Amplification of the her-2/neu gene occurs in approximately 25% of invasive ductal carcinomas of the breast. The first HER-2/neu-targeted approach to reach the clinic was trastuzumab, a humanized monoclonal antibody directed against the extracellular domain of the HER-2/neu protein. Trastuzumab therapy prolongs the survival of patients with metastático HER-2/neu-overexpressing breast cancer when combined with chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(228 citation statements)
references
References 30 publications
5
211
0
12
Order By: Relevance
“…Paradoxically, the targeted anti-HER2 therapy applied to the HER2-positive BC patients may be associated with an increased risk of BM development: four studies dedicated to the meta-analyses of large adjuvant trastuzumab trials found 1.3-to 1.8-fold increased risk of BM as the first metastatic site [58][59][60][61]. On the other side, the retrospective analysis showed no significant difference in BM development as the first site of recurrence amongst HER2-positive BC patients receiving 1-yearlong adjuvant trastuzumab against placebo (2 vs. 2%, respectively, P = 0.55) [62].…”
Section: The Targeted Therapy For Her2-positive Breast Cancer In Viewmentioning
confidence: 99%
“…Paradoxically, the targeted anti-HER2 therapy applied to the HER2-positive BC patients may be associated with an increased risk of BM development: four studies dedicated to the meta-analyses of large adjuvant trastuzumab trials found 1.3-to 1.8-fold increased risk of BM as the first metastatic site [58][59][60][61]. On the other side, the retrospective analysis showed no significant difference in BM development as the first site of recurrence amongst HER2-positive BC patients receiving 1-yearlong adjuvant trastuzumab against placebo (2 vs. 2%, respectively, P = 0.55) [62].…”
Section: The Targeted Therapy For Her2-positive Breast Cancer In Viewmentioning
confidence: 99%
“…However, even in the adjuvant setting up to 14% of patients discontinued trastuzumab treatment due to asymptomatic but protocol sufficient decreases in LVEF. In a recent metanalysis pooled results from five randomized adjuvant trials of adjuvant trastuzumab revealed an increased likelihood of cardiac toxicity (HR 2.45, 1.89-3.16 95% CI, P = 0.001) in the trastuzumab treated patients [18]. In the neoadjuvant setting, preliminary results of the NOAH trial, presented at the 2007 ASCO Breast Cancer Symposium, revealed drops in LVEF of 15.7% for the trastuzumab regimen versus 11.5% for the non-trastuzumab arm in patients with locally advanced breast cancer receiving concomitantly 3 cycles of doxorubicin-paclitaxel (60 mg/m 2 , 150 mg/m 2 q3w), 4 cycles of Paclitaxel (175 mg/m 2 q3w) and 3 cycles of cyclophosphamide/methotrexate/5-fluorouracil (C 600 mg/m 2 , M 40 mg/m 2 , F 600 mg/m 2 ) [19].…”
Section: Discussionmentioning
confidence: 99%
“…It manifests in several forms, ranging from acute arrhythmias and nonspecific electrocardiogram changes to decreases in LVEF. Beside age, hypertension, diabetes and coronary heart disease, trastuzumab treatment represents a significant risk factor for the development of anthracycline related cardiotoxicity [12,18]. The most severe complication is cardiomyopathy leading potentially to a permanent cardiac damage [20].…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen Tamoxifen was the first widely studied and approved endocrine therapy for HR-positive BC that is effective for the treatment of metastatic disease [47], reduces the risk of recurrence by about 50% when used as adjuvant therapy [5,6] and reduces the risk of BC by about 50% when used as preventive therapy in healthy women at high risk [16][17][18][19][20][21]. Ovarian suppression Chemotherapy-induced amenorrhea is a common complication of adjuvant chemotherapy, which is usually but not always indicative of menopause [63].…”
Section: Adjuvant Endocrine Therapymentioning
confidence: 99%
“…Randomized clinical trials have demonstrated that local excision resulted in comparable cure rates as mastectomy [4], and that adjuvant chemotherapy, endocrine therapy, and trastuzumab reduced local and systemic recurrence [5,6]. In order to bring about additional therapeutic advances, large, randomized clinical trials (CTs) remain critical.…”
Section: Introductionmentioning
confidence: 99%